Tanggung jawab Pemberitaan Pers dalam Perspektif Keadilan dan Hak Asasi Manusia di Indonesia - Samsul Wahidin (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Responsibility on press presentation is printed media has been unclear. Responsibility mechanism with "waterfall"characteristic has not yet reflected justice values based onthe principle that the doer holds the responsibility. Actually the responsibility has been regulated in the legislation. As a result, settlement on press presentation in printed media has not yet reflected justice and aprreciation of human rights. Settlement should be based on justmechanism by: establishing a special institution where dispute settlement on press responsibilities is implemented, and press Is ought to serve as well as possible people's indictments harm-full news sources. Press responsibility should distinctly stick the position of the individual of the newsmaker and be included in the editorial politic which constitutes and integral part of the press missions. Responsibility format based on water fall concept has to be affirmed by giving qualification who will bear the responsibility.